Comparison of Discovery Learning Models Assisted by Student Books and Videos on Student Motivation, Activity, and Learning Outcomes - Budi Setiawan; Adnan; Firdaus Daud (Jurnal Penelitian Pendidikan IPA, 2024)
The quality of learning requires innovation in teaching methods to improve student motivation, activity and learning outcomes. This pseudo-experimental research aims to determine the differences in motivation, activity, and learning outcomes of students taught using the Discovery Learning learning model assisted by student books (DL 1) and videos (DL 2). This study involved all students of class X at SMAN 8 Makassar and randomly selected class X.3 and X.7 as samples. Data were collected using a motivation questionnaire, observation sheet, and learning outcome test. The data collected were analyzed using descriptive statistics in the form of averages and inferential in the Manova Test. The results of this study show that there is a significant difference in the effect of the two treatments on student motivation, activity, and learning outcomes. Where students who were taught using a video-assisted discovery learning model were better than student books, the findings in this study imply that increasing the motivation, activity, and learning outcomes of students in high school should be given more attention through the application of appropriate learning models and media